Pengaruh Model Pembelajaran TGT Berbasis HOTS terhadap Hasil Belajar Matematika Kelas V SDN Mojosongo 3 Surakarta T.A 2023/2024 - Fujiantika, I.; Suryanti, H.H.S; Rizkasari, E. (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2024)
The purpose of this study was to determine the influence of the HOTS-based Teams Games Tournament learning model on mathematics leaming outcomes in class V SON Majosongo 3 Surakarta. The subjects in this study were all students in class VA and VB SON Mojosongo 3 Surakarta where class VA was the control class with 26 students and class VB was the experimental class with 26 students. Data collection techniques used were multiple choice questions (pretest and posttest), observation, and documentation. The instrument tests used were validity tests, reliability tests, question difficulty levels, and question discrimination tests. The data analysis technique used was the independent sample t-test.Based on the mean score of posttest results, the mean score in the experimental class was 83.96. While the mean score in the control class was 75.90. This showed that there was an increase in the experimental class after being given the HOTS-based Teams Games Tournament learning model. From the results of data analysis using the Independent Sample t-test, the sig value was obtained. 0.002 <0.05. The results of this study stated that